Zircon, titanite, and apatite (U‐Th)/He ages and age‐eU correlations from the Fennoscandian Shield, southern Sweden. Issue 7 (15th July 2017) - Guenthner, William R.; Reiners, Peter W.; Drake, Henrik; Tillberg, Mikael
Abstract: Craton cores far from plate boundaries have traditionally been viewed as stable features that experience minimal vertical motion over 100–1000 Ma time scales. Here we show that the Fennoscandian Shield in southeastern Sweden experienced several episodes of burial and exhumation from ~1800 Ma to the present. Apatite, titanite, and zircon (U‐Th)/He ages from surface samples and drill cores constrain the long‐term, low‐temperature history of the Laxemar region. Single grain titanite and zircon (U‐Th)/He ages are negatively correlated (104–838 Ma for zircon and 160–945 Ma for titanite) with effective uranium (eU = U + 0.235 × Th), a measurement proportional to radiation damage. Apatite ages are 102–258 Ma and are positively correlated with eU. These correlations are interpreted with damage‐diffusivity models, and the modeled zircon He age‐eU correlations constrain multiple episodes of heating and cooling from 1800 Ma to the present, which we interpret in the context of foreland basin systems related to the Neoproterozoic Sveconorwegian and Paleozoic Caledonian orogens. Inverse time‐temperature models constrain an average burial temperature of ~217°C during the Sveconorwegian, achieved between 944 Ma and 851 Ma, and ~154°C during the Caledonian, achieved between 366 Ma and 224 Ma. Subsequent cooling to near‐surface temperatures in both cases could be related to long‐term exhumation caused by either postorogenic collapse or mantle dynamics related to the final assembly of Rodinia and Pangaea. Our titanite He age‐eU correlations cannot currently be interpreted in the same fashion; however, this study represents one of the first examples of a damage‐diffusivity relationship in this system, which deserves further research attention. Key Points: Fennoscandian Shield zircon (U‐Th)/He ages are negatively correlated with effective uranium (eU), which is proportional to radiation damage These negative zircon He age‐eU correlations give long‐term constraints on multiple cycles of heating and cooling from 1.8 Ga to the present Titanite (U‐Th)/He ages are also negatively correlated with eU; we provide some of the first evidence for damage effects on titanite He ages